Right in France 1890-1919 - Shapiro, David .(ed.) (London, 1962)
After 1877 the Right in France was excluded from effective political power. In the 1890's the rise of an organized socialist movement limited further the Right's freedom of manoeuvre. Boulanger had been the last political figure to unite, although with difficulty, both Left and Right in protest against the Centre. The three studies in this volume are designed to illustrate the reaction of the Right to this new situation.
Keywords: Politics and Government